Jacques Cousteau, and the Amazon Expedition: Environmental Imagination and the Brazilian press In the 1980’s - Klanovicz, Jo (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2026)
This paper examines Jacques Cousteau’s Amazon Expedition (1982-1983) and its representation in the Brazilian press. Employing a methodological framework of discourse and media analysis, the study scrutinizes the expedition’s documentary, its coverage in newspapers like the Jornal do Brasil, and the associated bibliographic production. It positions these materials as "environmental texts" to decode the specific environmental imagination they fostered. The analysis reveals that the expedition, framed by a colonialist and Eurocentric perspective, did not produce a cohesive or scientifically rigorous understanding of the Amazon. Instead, it generated ambiguous perceptions, promoting an "on-demand" nature spectacle that emphasized exoticism and grandeur. The paper concludes that Cousteau’s work, while documenting environmental degradation, ultimately offered a superficial critique. It failed to engage meaningfully with the region’s historical socio-biodiversity and the complex socio-environmental transformations already underway, thereby reinforcing a foreign, mediatized, and consumable image of the Amazon that aligned with both developmentalist interests and a burgeoning global environmentalism.